Development of a computer service for assessing and analysing the readiness of freestyle athletes - Zdanovich, O.S.; Zebzeev, Vl.V.; Paramonova N.А. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to create a special computer service for automating the assessment and analysis of freestyle skiers’ preparedness. Methods and structure of the study. The computer program is written in HTML, CSS, PHP, and JavaScript. Development environment: Visual Studio 2022 Community, Visual Studio Code. Database: PostgreSQL. Client: HTML, CSS, JavaScript. Server: PHP, PostgreSQL. Control indicators are determined based on the results of a theoretical analysis of the research problem. The computer service was successfully tested in scientific and methodological support activities for the training of athletes of the Russian national sports team during 2025. Results and conclusions. A computer program developed to assess and analyse the preparedness of freestyle athletes has been implemented in sports training with the help of a number of interrelated modules: administration and information protection; personalised information about athletes; preparedness monitoring; model characteristics configuration; video archive; analytics; creation and correction of sports training plans, which creates favourable opportunities for improving the effectiveness of management from pedagogical influences in freestyle.